Cell cycle arrest evidence, parasiticidal and bactericidal properties induced by L-amino acid oxidase from Bothrops atrox snake venom - Alves Paiva, Raquel de Melo (2011)
The present article describes an L-amino acid oxidase from Bothrops atrox snake venom as with antiprotozoal activities in Trypanosoma cruzi and in different species of Leishmania (Leishmania braziliensis, Leishmania donovani and Leishmania major). Leishmanicidal effects were inhibited by catalase, suggesting that they are mediated by H2O2 production. Leishmania spp. cause a spectrum of diseases, ranging from self-healing ulcers to disseminated and often fatal infections, depending on the species involved and the host's immune response. BatroxLAAO also displays bactericidal activity against both Gram-positive and Gram-negative bacteria. The apoptosis induced by BatroxLAAO on HL-60 cell lines and PBMC cells was determined by morphological cell evaluation using a mix of fluorescent dyes. As revealed by flow cytometry analysis, suppression of cell proliferation with BatroxLAAO was accompanied by the significant accumulation of cells in the G0/G1 phase boundary in HL-60 cells. BatroxLAAO at 25 mu g/mL and 50 mu g/mL blocked G0-G1 transition, resulting in G0/G1 phase cell cycle arrest, thereby delaying the progression of cells through S and G2/M phase in HL-60 cells. This was shown by an accentuated decrease in the proportion of cells in S phase, and the almost absence of G2/M phase cell population. BatroxLAAO is an interesting enzyme that provides a better understanding of the ophidian envenomation mechanism, and has biotechnological potential as a model for therapeutic agents. (C) 2011 Elsevier Masson SAS. All rights reserved.